Pengaruh Besar Arus Listrik pada Proses Wire Edm Terhadap Profile Error Involute Roda Gigi Lurus - Gapsari, Femiana; Sugiarto, Sugiarto; Bagus, Nugroho (Jurnal Rekayasa Mesin, 2011)
Wire Electric Discharge Mechine (EDM) is one of non conventional metal cutter machines. This machine is used to form machine components which has complex form and needs high precision. One of the machinery parameters which influences cutting precision on Wire EDM is the amount of pulse current. The form of involute profile of gear is a form which has complexity and high precision which often changes the form of geometry profile. This studyis aimed at investigating the extent of the influence of the amount of current parameter on Wire EDM towards the profile error involute spur gear. Thi study is experimental design, the independent variable used is pulse current with variation of 3 ampere, 4 ampere, 5 ampere, 6 ampere, and 7 ampere. The dependent variable in this study is profile error involute spur gearwhich later will explain the extent of cutting distortion. The result of this study showed that the higher the electric current, the higher the level of profile error involute spur gear. This means that the level of the precision is getting lower. The level of the lowest profile error involute, which is 0.0907 mm, found at 3 ampere pulse current, while the highest level of profile error involute, which is 0.1256 mm, found at 7 ampere electric current.Keywords: wire edm, pulse current, profile error involute, spur gear.